PROGRAMAÇÃO CNC ASSOCIADA À AUTOMATIZAÇÃO DE ENSAIOS GEOMÉTRICOS DE QUALIFICAÇÃO DE MÁQUINAS-FERRAMENTAS - Benini, Lucas; Ferreira, Thiago A.; Heimburg, Julio V.; Eckhardt, Moacir; Ribeiro, Luis F. M. (Salão do Conhecimento, 2013)
Resumo